Endogamous Marriages among the Kiai in Sukorejo Islamic Boarding School, Situbondo: A Phenomenological Approach in the Perspective of Multicultural Fiqh - Mirwan, Mirwan; R. Fakhrurrazi, R. Fakhrurrazi; Al Munawar, Faishal Agil (Jurnal Adabiyah, 2023)
This research discusses the meaning of endogamous marriages among Kiai in the environment of Sukorejo Islamic Boarding School, Situbondo, from a multicultural fiqh perspective. The Kiai adapt their religious understanding to the social realities they face, and their endogamous marriages have both religious and social motives. Lineage, religiousness, knowledge, and the social culture of potential partners serve as indicators of ideology, orientation, and character in choosing a spouse. The concept of kafa'ah sets clear boundaries according to the situation and conditions within the context of endogamous marriages. The research method used is an interpretative phenomenological approach, utilizing data sources from observations and in-depth interview techniques. The perspective of multicultural fiqh reveals that the endogamous marriages among the Kiai in the Sukorejo Islamic Boarding School environment embody the values of Sufistic social fiqh. ملخصة يتناول هذا الكتاب معنى زواج الأقارب لعلماء الدين الكياي في مدرسة سوكوريجو سيتوبوندو من منظور الفقه المتعدد الثقافات. يقوم علماء الدين الكياي بتكييف فهمهم للدين مع الواقع الاجتماعي الذي يواجهه، ولديهم دوافع دينية واجتماعية للزواج الأسري. تُستخدم معايير المنح والعلم الاجتماعي للشريك تضع مفهوم حدودًا واضحة وواقعية للحالة والظروف في سياق معنى زواج الأقارب. تظهر منظور منظور متعدد الثقافات في الزواج الأسري لعلماء الدين الكياي في مدرسة سوكوريجو سيتوبوندو يحتوي على قيم اجتماعية صوفية. طرق البحث الظاهري التفسيري مع مصادر البيانات من الملاحظات وتقنيات المقابلات العميقة. المفتاحية الكلمات : الظواهر ; الفقه متعدد الثقافات ; زواج الأقارب ; كياي بالمدرسة الداخلية الإسلامية Abstrak Penelitian ini membahas makna pernikahan endogami Kiai di lingkungan pondok pesantren Sukorejo Situbondo dari perspektif fiqh multikultural. Para Kiai melakukan adaptasi pemahaman agamanya dengan realitas sosial yang dihadapinya, dan pernikahan endogami mereka memiliki motif agama dan sosial. Standar nasab, keberagamaan, keilmuan, dan kultur sosial calon pasangan dijadikan sebagai petanda ideologi, arah orientasi, dan karakter dalam memilih pasangan. Konsep kafa`ah menjadi tegas batasannya sesuai dengan situasi dan kondisi dalam konteks pernikahan endogami. Metode penelitian yang digunakan adalah pendekatan fenomenologi interpretatif dengan sumber data dari observasi dan teknik wawancara mendalam. Perspektif fiqh multikultural menunjukkan bahwa pernikahan endogami Kiai di lingkungan pondok pesantren Sukorejo Situbondo mengandung nilai-nilai fiqh sosial sufistik. Kata Kunci: Fenomenologi; Fiqh Multikultural; Pernikahan Endogami; Kiai Pesantren